The Effect of Vitamin D Administration on Androgen Levels in Addition to Metformin Treatment in Adolescent Girls with Hyperandrogenism - Esranur Çiğ; Muge Atar; Ozgur Pirgon (Galenos Publishing House, 2022)
This retrospective study was planned to examine the relationship between glucose metabolism, androgen and lipid profiles after vitamin D and metformin treatments in adolescent girls with hyperandrogenism. Forty-five adolescent female patients diagnosed with hyperandrogenism were divided into three groups. The first group of patients was given metformin (M), the second group was given metformin and vitamin D drops (MdD), and the third group were those who received oral metformin and vitamin D ampoules (MsD). Biochemical and hormonal parameters at the end of 8 weeks were compared statistically. The vitamin D level was higher in the metformin-vitamin D stoss treated group than metformin-vitamin D drops. There was a positive correlation between vitamin D and SHBG in the metformin group (r =0.65, p<0.01). A significant correlation was observed between triglyceride and insulin in both groups given vitamin D, and there was a decrease in these two values (p<0.05). There was a positive correlation between total testosterone and Alanine transaminase (ALT) in the MsD group (p<0.05). Additionally, a positive correlation was observed between SHBG and HDL-cholesterol in three groups. There was a significant correlation between androgen and lipid parameters in the 8-week metformin and vitamin D treated groups. Long-term studies using high-dose vitamin D are needed to support our results.